E-learning center of excellence as a service on a private cloud implementation for Jordanian universities - S. AlTarawneh, Mokhled; Bani Salamah, Jamal (International Journal of Engineering and Technology, 2018)
There is a need to design a collaboration infrastructure for Jordanian Universities’ to meet their technological needs, use benefit of advanced software to solve a lot of complexes problems quickly and at a lower cost. This paper presents a suggested solution based on cloud computing concepts and describes the structure of the proposed platform to set up an E-Learning center of excellence as service. The authors attempted to offer cloud computing for e-learning service, build a center of excellence in E-learning, and prepare for active exploration model from the following aspects: architecture, construction, and external interface, over and above investigate the factors affecting universities’ willingness to use cloud computing in many educational services using quantitative research approach as well empirical studies.
Keywords: Cloud Computing; E-Learning; Cloud Deployment Models; Center of Excellence.